2020
DOI: 10.2174/1871530319666190626143301
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Peroxidase Antibody (TPO) as a Predictor of Radiation Induced Thyroid Dysfunction Among Nurses and Technicians Working in Mansoura Specialized Medical Hospital: Cross Sectional Study

Abstract: Background:: Thyroid gland is a probable goal tissue for radiation-related injury. Occupational exposure to ionizing radiation leads to thyroid dysfunction and exposure to high dose may lead to thyroid carcinoma. Objective:: Evaluation of the role of Thyroid peroxidase antibody as a predictor for thyroid dysfunction among nurses and technicians in the radiology department in Mansoura Specialized Medical hospital (MSMH). Subjects and Methods:: Subjects were Nurses and technicians who are working in (MSMH) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
1
5
1
Order By: Relevance
“…A recent study by Albehairy A et al [ 31 ] is constant with the present study, indicating that working personnel in the radiation field are positive for anti-TPO. In autoimmune thyroid disorders, thyroid autoantibodies such as a thyroid-stimulating antibody, anti-thyroglobulin antibody, and anti-thyroperoxidase antibody can be found.…”
Section: Discussionsupporting
confidence: 90%
“…A recent study by Albehairy A et al [ 31 ] is constant with the present study, indicating that working personnel in the radiation field are positive for anti-TPO. In autoimmune thyroid disorders, thyroid autoantibodies such as a thyroid-stimulating antibody, anti-thyroglobulin antibody, and anti-thyroperoxidase antibody can be found.…”
Section: Discussionsupporting
confidence: 90%
“…Some of the factors examined in this study include age, gender, race/ethnicity, family history of thyroid diseases, cigarette smoking, and ionizing radiation exposure. Age in our study was not a significant predictor of TPOAb; however, most (95%; 266 of 278) of our study participants are in a relatively restrictive age range (30-64 years) where TPOAb are the highest levels compared to the extreme of ages [ 23 , 27 , 29 ]. A preponderance of TPOAb and autoimmune diseases is found among females than among males [ 13 , 29 ], and risk is increased by occupational exposure such as radiation [ 29 ].…”
Section: Discussioncontrasting
confidence: 59%
“…Reported occupational radiation exposure increased the odds of being TPOAb positive by 16% in our study population, but this finding was not significant. Several studies have shown an association between radiation exposure including medical radiation and increased risk of autoimmune thyroid disorder [ 13 , 23 , 44 ]. A dose-effect relation between the high dose of radiation exposure and autoimmune thyroid disease has been reported; however, firefighters are not typically exposed to high doses of radiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bipolar coagulation has been widely employed in clinical treatment due to its clear surgical field and low intraoperative blood loss and has achieved significant clinical effects [ 16 18 ]. However, the propensity for various complications such as hematoma, incision infection, hypothyroidism, and hoarseness after thyroid surgery, combined with the negative emotions and pain, poses a great psychological pressure on the patients, which results in a somber prognosis [ 19 , 20 ]. It has been clinically discovered that proper nursing measures for thyroid patients after treatment can effectively alleviate the patients' negative emotions, improve the patient's quality of life and self-care ability, which is conducive to creating a harmonious nurse-patient relationship and promoting a quick recovery.…”
Section: Discussionmentioning
confidence: 99%